CLONACIÓN DE PROGENIES DE ALCORNOQUES PLUS DE CUATRO REGIONES DE PROCEDENCIA MEDIANTE EMBRIOGÉNESIS SOMÁTICA PARA LA OBTENCIÓN DE MATERIALES FORESTALES DE REPRODUCCIÓN - Cuenca, B.; López, C.; Pato, B.; Ocaña, L.; Santos, M. I.; Manzanera, J. A.; Pintos, B.; Bueno, M. A. (IV Congreso Forestal Español, 2005)
Se ha realizado una selección fenotípica individual de árboles plus de alcornoque en los rodales selectos establecidos por el Instituto del Corcho, la Madera y el Carbón Vegetal (ICMC, Junta de Extremadura) en cuatro regiones de procedencia: Montes de Toledo-Villuercas, Sierra Morena Occidental, Sierra de San Pedro, y Norte de Cáceres-Salamanca. De los árboles seleccionados se han recogieron estaquillas en primavera de 2002 y 2003, y bellotas inmaduras durante el verano de 2002, 2003 y 2004. De las estaquillas se establecieron inicialmente 48 clones mediante cultivo de yemas axilares (MANZANERA y PARDOS, 1990). La elevada edad de los árboles hizo imposible la estabilización y mantenimiento de los cultivos y actualmente sólo sobrevive 1 de los clones. De los embriones cigóticos inmaduros, según protocolo de BUENO et al. (1992), se consiguió inducir embriogénesis somática en los 55 árboles muestreados de los 61 seleccionados. Estas líneas son regularmente subcultivadas, y los embriones obtenidos madurados, germinados y aclimatados para el establecimiento de ensayos de progenie con propósito de disponer de materiales de mejora. En enero de 2005 se estableció la primera finca de ensayo y actualmente se dispone de 1400 vitroplantas más para el establecimiento de nuevas parcelas. Palabras
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español
Keywords: Corcho; cultivo in vitro; embriones; Quercus suber; selección

Cytological analysis of early microspore divisions leading to gametic embryo formation in Quercus suber L. anther cultures - Pintos, B.; Manzanera, J. A.; Bueno, M. A. (Acta Physiologiae Plantarum, 2005)
The cor re la tion be tween the phenologic stage of the in flo res - cence and the microspore de vel op ment stage was stud ied. Cyto log i cal ex am i na tions of the de vel op ment of micro spores dur - ing in vi tro an ther cul ture of cork oak (Quercus suber L.), were car ried out dur ing the first four weeks of cul ture. To ob serve the di vi sion oc cur ring in the micro spores, an thers were taken ran domly from the cultures after heat shock treatment and were stained with DAPI. Most of the an thers re spond ing to a heat stress treat ment con tained 91 % vacuolated micro spores, in di cat ing that this de vel op men tal stage is re spon sive to embryo genesis in duc tion in cork-oak micro spores. Af ter the heat shock treat ment some cork-oak micro spores were in duced and ini ti ated the embryogenic path way with the oc cur rence of nu mer ous sym met ric mi to sis, pro duc ing struc tures with two to ten or more nu clei. These lead to the for ma tion of high num - bers of multicellular cork-oak micro spores (pro-em bryos). Twenty-forty days af ter in duc tion, small white glob u lar and cotyledonal em bryos were ob served, which fur ther de vel oped root and shoot, re gen er at ing plantlets.
Keywords: anther culture; Cork oak; microspore embryogenesis; Quercus suber

Haploid origin of cork oak anther embryos detected by enzyme and RAPD gene markers. - Bueno, M. A.; Agundez, M. D. (International Journal of Plant Sciences, 2000)
Examines the haploid origin of cork oak anther embryos using enzyme and RAPD gene marker analysis. Exploration of the gene coding of shikimate dehydrogenase; Factor influencing the non-identification of another genotypes by isozyme analysis; Implication of detected banding patterns for the existence of multiple microspore origins.
Keywords: Cork oak; Haploid; Quercus suber; RAPD markers

Plant regeneration through somatic embryogenesis in Quercus suber - Bueno, M. A.; Astorga, R.; Manzanera, J. A. (Physiologia Plantarum, 1992)
Cork oak (Quercus suber L.) zygotic embryos, endosperm and ovules were treated with different concentrations of 2,4-D for induction of somatic embryos. Plant material was collected during the embryo development season, from June to September. Immature embryos proved to be the most reactive initial explant. Callus and somatic embryos developed a few weeks after the beginning of the 2,4-D treatment. For embryo development experiments, different growth regulators and cold and desiccation treatments were tested. Cold storage of somatic embryos matured in vitro at 5°C was the best treatment for breaking dormancy.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; plant regeneration; Quercus suber; Somatic embryogenesis; tissue culture